2018
DOI: 10.1111/ajt.14697
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health in women following abdominal organ transplant

Abstract: Fertility is commonly impaired in women with end-stage kidney and liver disease, although most women will have restoration of fertility within 1 year of transplant. Family planning is therefore critical to discuss with reproductive-aged transplant recipients in the early posttransplant period, in order to ensure timely initiation of contraception, and optimal timing for conception. For women seeking pregnancy, the risks to the mother, graft, and baby should be discussed, including evaluation of immunosuppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 51 publications
1
49
0
2
Order By: Relevance
“…Fertility, which is often compromised in chronic liver disease, can be restored rapidly after liver transplantation. While much has been published about fertility and pregnancy risks in transplant recipients, [14][15][16] reported being actively counseled against pregnancy by one or more providers at any point in time. 17 In our study, we found significant deficiencies in the overall documentation of reproductive health counseling in post-transplant Note: Race (P = 1.00) and cause of liver disease were not associated with reproductive counseling (P = 1.00).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertility, which is often compromised in chronic liver disease, can be restored rapidly after liver transplantation. While much has been published about fertility and pregnancy risks in transplant recipients, [14][15][16] reported being actively counseled against pregnancy by one or more providers at any point in time. 17 In our study, we found significant deficiencies in the overall documentation of reproductive health counseling in post-transplant Note: Race (P = 1.00) and cause of liver disease were not associated with reproductive counseling (P = 1.00).…”
Section: Discussionmentioning
confidence: 99%
“…While much has been published about fertility and pregnancy risks in transplant recipients,[14][15][16] there are limited data about reproductive health counseling in these high-risk individuals and additional studies are needed. While much has been published about fertility and pregnancy risks in transplant recipients,[14][15][16] there are limited data about reproductive health counseling in these high-risk individuals and additional studies are needed.…”
mentioning
confidence: 99%
“…Use of certain contraception, such as estrogen‐containing CHCs in recipients with complicated transplants (acute or chronic graft failure, rejection, or cardiac allograft vasculopathy) raises the threshold of concern to CDC category 4 (unacceptable risk). CHCs are considered acceptable for use in the absence of decompensated cirrhosis, blood pressure < 130/90 mm Hg, normal renal function (GFR > 90) and absence of cardiac allograft vasculopathy 16 …”
Section: Types Of Contraceptionmentioning
confidence: 99%
“…In 1 study, the concentration of corticosteroids within the breast milk of women taking 10-80 mg of prednisolone per day was between 5% and 25% of maternal serum concentrations. 26…”
Section: Steroidsmentioning
confidence: 99%
“…There is not enough information on sirolimus, everolimus, and belatacept. [25][26][27][28][29][30][31][32] WOMEN ON DIALYSIS Similar to women with CKD, there are minimal data available on lactation and breast milk composition in women on dialyisis. There is 1 study that directly looked at human milk composition in a woman on hemodialysis (HD).…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%